2018
DOI: 10.1021/acs.iecr.8b03065
|View full text |Cite
|
Sign up to set email alerts
|

From Crystal to Adsorption Column: Challenges in Multiscale Computational Screening of Materials for Adsorption Separation Processes

Abstract: Multiscale material screening strategies combine molecular simulations and process modeling to identify the best performing adsorbents for a particular application, such as carbon capture. The idea to go from the properties of a single crystal to the prediction of material performance in a real process is both powerful and appealing; however, it is yet to be established how to implement it consistently. In this article, we focus on the challenges associated with the interface between molecular and process leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 64 publications
2
110
0
Order By: Relevance
“…Although these simple properties are important indicators of the performance of these materials for adsorptionbased engineering applications, these metrics do not completely determine process-level objectives. [376][377][378] For instance, the usable capacity and selectivity of CO 2 are commonly used performance metrics for CO 2 capture applications, while the overall process objectives are the cost of capturing and recovering the CO 2 ($/g CO 2 ) and the productivity of the material, 378 both under CO 2 purity and recovery constraints. Since the improvements in equilibrium adsorptive selectivity and usable capacity do not necessarily translate into better process performance, we envisage the integration of process-level simulations and molecular simulations, feeding innate material properties obtained from molecular simulations into processlevel (larger length scale) simulations to account for heat and mass transfer kinetics, pressure drops in columns, etc.…”
Section: Multi-scale Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these simple properties are important indicators of the performance of these materials for adsorptionbased engineering applications, these metrics do not completely determine process-level objectives. [376][377][378] For instance, the usable capacity and selectivity of CO 2 are commonly used performance metrics for CO 2 capture applications, while the overall process objectives are the cost of capturing and recovering the CO 2 ($/g CO 2 ) and the productivity of the material, 378 both under CO 2 purity and recovery constraints. Since the improvements in equilibrium adsorptive selectivity and usable capacity do not necessarily translate into better process performance, we envisage the integration of process-level simulations and molecular simulations, feeding innate material properties obtained from molecular simulations into processlevel (larger length scale) simulations to account for heat and mass transfer kinetics, pressure drops in columns, etc.…”
Section: Multi-scale Modelingmentioning
confidence: 99%
“…to properly rank materials. 378,379 However, (i) process-level modeling requires many physical properties of the material to be known, and (ii) often, processlevel detriments to material performance can be corrected via engineering, e.g., poor thermal conductivity can be addressed by incorporating heat exchangers into the process.…”
Section: Multi-scale Modelingmentioning
confidence: 99%
“…Although these simple properties are important indicators of the performance of these materials for adsorptionbased engineering applications, these metrics do not completely determine process-level objectives. [285][286][287] For instance, the usable capacity and selectivity of CO 2 are commonly used performance metrics for CO 2 capture applications, while the overall process objectives are the cost of capturing and recovering the CO 2 ($/g CO 2 ) and the productivity of the material, 287 both under CO 2 purity and recovery constraints. Since the improvements in equilibrium adsorptive selectivity and usable capacity do not necessarily translate into better pro-cess performance, we envisage the integration of process-level simulations and molecular simulations, feeding innate material properties obtained from molecular simulations into processlevel (larger length scale) simulations to account for heat and mass transfer kinetics, pressure drops in columns, etc.…”
Section: Multi-scale Modelingmentioning
confidence: 99%
“…to properly rank materials. 287 For example, First et al 286 combined molecular simulations [to predict adsorption isotherms] and pressure swing adsorption process modeling and optimization of e.g., the column length and pressure of adsorption and desorption, under methane recovery and purity constraints, to rank zeolites for CO 2 capture from natural gas. Interestingly, the authors found "no clear correlation between the overall cost and materialcentric metrics, such as adsorption selectivity".…”
Section: Multi-scale Modelingmentioning
confidence: 99%
“…17,21,22 In this approach, key characteristic properties of adsorbent materials, such as equilibrium adsorption isotherms and micropore diffusivity of gas components, are calculated from microscale molecular simulations, however the actual performance of materials (e.g. productivity, energy consumption, purity and recovery of the product) is evaluated at the process level 22,23 using optimization of PSA/VSA processes. The current research thrust is to extend these strategies to screen a large number of porous materials available within recently assembled databases of porous solids, such as CSD, 24 CoRE-MOFs 25 and DZS.…”
Section: Introductionmentioning
confidence: 99%